Which Asymmetric Tibial Component Is Optimally Designed for Calipered Kinematically Aligned Total Knee Arthroplasty? - Nedopil, Alexander J.; Zamora, Tomas; Delman, Connor; Howell, Stephen M.; Hull, Maury L. (The Journal of Knee Surgery, 2021)
Calipered kinematically aligned (KA) total knee arthroplasty (TKA) restores the patient's prearthritic joint lines and sets internal-external rotation of the tibial component parallel to the flexion-extension (FE) plane, which is not a mechanical alignment (MA) target. Two asymmetric tibial components designed for MA set the tibial component to either a femoral component (FC) target or a tibial tubercle (TT) target. The study determined the optimal asymmetric tibial component to use with KA as the one with smaller IE deviation from the MA target, greater coverage of tibial resection, and lower incidence of cortical overhang. The study included 40 patients treated with bilateral calipered KA TKA with different asymmetric tibial components in opposite knees. A best-fit of a kinematic tibial template to the tibial resection set the template's slot parallel to the knee's FE plane. Each asymmetric tibial component's anterior-posterior (AP) axis was set parallel to the slot. Computer tomography analysis determined the IE deviation (−internal/+ external) of each tibial component from its MA target, tibial resection coverage by the baseplate and insert, and incidence of cortical overhang. The patient-reported Forgotten Joint Score (FJS) and Oxford Knee Score (OKS) determined outcomes. The mean IE deviation from the MA target was 2 degrees external for the FC-target asymmetric tibial component and −8 degrees internal for the TT-target asymmetric tibial component (p < 0.001). Tibial resection coverage by the baseplate (insert) was 88% (84%) for the FC target and 84% (79%) for the TT target (p < 0.001 for baseplate and insert). The FC target insert covered 3 mm more of the posterolateral resection (p < 0.001). Posteromedial coverage was comparable. The incidence of cortical overhang was 2.5% for each baseplate. There was no difference in FJS and OKS. When performing calipered KA, the more optimal design was the asymmetric tibial component with the FC target because of the smaller deviation from its MA target and the greater coverage of the tibial resection by the baseplate and insert.
Keywords: knee arthroplasty; total knee replacement; kinematic alignment; tibial coverage; flexion-extension plane